SYNTHESIS OF CUPRUM OXIDE NANOPARTICLES IN WATER SUSPENSIONS - Garibyan, Boris; Kohlert, Victoria (Revista Inclusiones, 2020)
In this study, plasma discharge in a liquid at intensive ultrasonic field above the cavitation threshold has been proven to be of great interest for synthesis of cupric oxide nanoparticles with narrow particle size distribution. Further exploration of synthesized nanoparticles has demonstrated that the factor of ultrasonic cavitation during the synthesis substantially affects optical characteristics of nanoparticles.